Study the Nuclear Structure of Some Cobalt Isotopes - Ban Sabah Hameed; Basim Khalaf Rejah (مجلة بغداد للعلوم, 2022)
The nuclear structure of some cobalt (Co) isotopes with mass number A=56-60 has been studied depending on the effect of some physical properties such as the electromagnetic properties effects, such as, elastic longitudinal form factors, electric quadrupole moments, and magnetic dipole moments. The fp model space is used to present calculations using GXFP1 interaction by adopting the single particle wave functions of the harmonic oscillator. For all isotopes under consideration, the 40Ca nucleus is regarded as an inert core in fp model-space, while valence nucleons are moving through 1f7/2, 2p3/2, 1f5/2, and 2p1/2 orbits. The effects of core-polarization are obtained by the first order core polarization through a microscopic theory. In addition, the core polarization was added using the effective charge and effective g factors to calculate quadrupole and magnetic moments, respectively. The results obtained are compared to experimental data that is accessible.